An analysis of the interaction between section 7(8) and section 31(2) of the Income Tax Act No. 58 of 1962 when applied to non-interest-bearing loans from resident natural persons to connected non-resident trusts - Hewitt, Mark John (Stellenbosch : Stellenbosch University, 2020)
Thesis (MAcc)--Stellenbosch University, 2020.